Primary Myelofibrosis Presenting as Extramedullary Hematopoiesis in a Transplanted Liver Graft: Case Report and Review of the Literature - Ghulam Rehman Mohyuddin; Abdulraheem Yacoub (Case Reports in Hematology)
Primary myelofibrosis (PMF) commonly results in extramedullary hematopoiesis (EMH) in the spleen and liver as well as a variety of other organs. We present a first report of a unique presentation of PMF in a liver transplant recipient patient as EMH in the transplanted liver graft. A 76-year-old man with history of cryptogenic cirrhosis received cadaveric liver transplantation in 1996. He maintained a normal graft function and stable hematologic parameters until 2013 when he presented with anemia and progressive fatigue. Extensive work-up did not identify the etiology of the recent decline in his hemoglobin; thus a liver biopsy was done which showed findings of EMH within the sinusoids with increased megakaryocytes, some with atypical morphology. A BM biopsy revealed a hypercellular marrow, moderately increased reticulin fibrosis, and features consistent with primary myelofibrosis. Abdominal imaging showed a normal-size spleen and did not identify any sites of EMH outside of the liver. The diagnosis of myelofibrosis was thus made, and this case demonstrated predominant tropism to a transplanted liver graft with absence of EMH elsewhere. We would thus like to emphasize that findings of EMH in subjects with no preexisting hematologic neoplasm should warrant close follow-up and assessment.